How to administer near-infrared spectroscopy in critically ill neonates, infants, and children - Bruns, Nora; Moosmann, Julia; Münch, Frank; Dohna-Schwake, Christian; Wölfle, Joachim; Cesnjevar, Robert; Dittrich, Sven; Felderhoff-Müser, Ursula; Müller, Hanna (Journal of Visualized Experiments, 2020)
Near infrared spectroscopy (NIRS) calculates regional tissue oxygenation (rSO2) using the different absorption spectra of oxygenated and deoxygenated hemoglobin molecules. A probe placed on the skin emits light that is absorbed, scattered, and reflected by the underlying tissue. Detectors in the probe sense the amount of reflected light: this reflects the organ-specific ratio of oxygen supply and consumption-independent of pulsatile flow. Modern devices enable the simultaneous monitoring at different body sites. A rise or dip in the rSO2 curve visualizes changes in oxygen supply or demand before vital signs indicate them. The evolution of rSO2 values in relation to the starting point is more important for interpretation than are absolute values. A routine clinical application of NIRS is the surveillance of somatic and cerebral oxygenation during and after cardiac surgery. It is also administered in preterm infants at risk for necrotizing enterocolitis, newborns with hypoxic ischemic encephalopathy and a potential risk of impaired tissue oxygenation. In the future, NIRS could be increasingly used in multimodal neuromonitoring, or applied to monitor patients with other conditions (e.g., after resuscitation or traumatic brain injury).
CRIS-Team Scopus Importer:2020-09-18